Identification of Somatic Mutations in Papanicolaou Smear DNA and Plasma Circulating Cell-Free DNA for Detection of Endometrial and Epithelial Ovarian Cancers: A Pilot Study - Jiang, Xuan; Li, Weihua; Yang, Jiaxin; Wang, Shuzhen; Cao, Dongyan; Yu, Mei; Shen, Keng; Bai, Jian; Gao, Yang (Frontiers in Oncology, 2020)
Objectives The aim of this study was to identify tumor-derived DNA from Papanicolaou (Pap) smear and plasma specimens collected from patients with endometrial cancer or atypical hyperplasia (EC/AH) or epithelial ovarian cancer (OC). Methods Tumor tissues, peripheral blood, and Pap smear samples were collected from patients with EC/AH and patients with epithelial OC. Somatic mutations of tumor specimens in EC/AH and OC were examined by whole-exome sequencing using a 127-driver gene panel from The Cancer Genome Atlas (TCGA). A nine-gene EC/AH panel and an eight-gene OC panel were established based on the identified significantly mutated genes in the EC/AH and OC tumor specimens. Circulating single-molecule amplification and resequencing technology (cSMART) was applied to evaluate somatic mutations in Pap smear DNA and plasma circulating cell-free DNA (ccfDNA) using the EC/AH and OC gene panels. Results In EC/AH group, there existed 22 tumors and 14 of the 22 tumors contributed hot spot mutations for the EC/AH nine-gene panel. In the Pap smear subgroup, all 21 Pap smears tested positive. Nine out of 11 (81.8%) identified the same gene mutations with their matched tumors and the remaining 10 Pap smears all tested positive. In the plasma subgroup, 10 out of 26 (38.5%) plasmas tested positive. One out of 13 (7.7%) identified the same gene mutation with its matched tumor and 5 out of the remaining 13 plasmas (38.5%) tested positive. In OC group, there existed 17 tumors and 16 of the 17 tumors contributed hot spot mutations for the OC eight-gene panel. In the Pap smear subgroup, all 11 Pap smears tested positive. Five out of 10 (50.0%) identified the same gene mutations with their matched tumors and the remaining one Pap smear also tested positive. In the plasma subgroup, all 22 plasmas tested positive. Ten out of 14 (71.4%) identified the same gene mutation with their matched tumors and the remaining 4 plasmas all tested positive. Conclusions Tumor-derived DNA can be detected in Pap smears and plasmas from patients with EC/AH or epithelial OC. Using a small gene-panel, early detection of EC/AH and OC might be promising. However, the value of plasma ccfDNA for EC/AH requires further investigation.